The Moderating Role of Board Diversity and COVID-19 on ESG Dimension Relationship with Financial Performance - Manik, Sari Renata (Ekspektra : Jurnal Bisnis dan Manajemen, 2023)
ESG (environmental, social, and governance) had been a field of interest globally these past few years. The purpose of this study was to evaluate impact of each ESG dimension using content analysis method to corporate financial performance (CFP) with board diversity and COVID-19 as moderating variables. Using panel data set consisting of sample of 39 nonfinancial companies listed in ESGSKEHATI during the period 2017 – 2021, it was found that ESG dimension simultaneously had significant positive impact on CFP proxied by ROA. In addition to that, it was found that interaction of social dimension with ROA weakened through moderating role of board gender diversity. In other words, ROA was expected to decrease when social disclosure items were maintained by the presence of this gender diversity. In contrast, interaction of social dimension with market value strengthened through moderating role of board gender diversity. Tobin’s Q was expected to increase when social disclosure items were maintained by the presence of this gender diversity. The other finding showed that COVID-19 pandemic strengthens interaction of social dimension with Tobin’s Q. Stakeholders need to be aware of potential impact of each ESG dimension, benefits of having board diversity, and anticipating pandemic condition impact on CFP.